Keterlibatan Kerja Karyawan di Industri Hospitality Pariwisata: Analisis Bibliometrik - Suprina, Rina; Senen, Syamsul Hadi; Rofaidah, Rofi (Jurnal Manajemen, 2022)
The literature that discusses HR management practices in the hospitality and tourism industry is still relatively limited, even though there are many issues related to human resources in the hospitality and tourism sectors. This paper aims to examine the literature related to employee engagement practices in the hospitality and tourism sectors and their impact on other constructs. To obtain literature data, the publish or perish software was used and the Google Scholar database was selected. The keyword used is "work engagement hospitality tourism". In the initial search, 200 literatures were obtained from 2016 to 2021. Then the 200 literatures were selected so that 75 references were obtained. Using the Mendeley reference manager and Publish or Perish software, data on the most cited articles, top-tier journals, and top publishers were collected. Furthermore, the 75 references were processed using the VOS Viewer so that cluster data was obtained which consisted of the items that appear in each cluster. Overlay visualization, density visualization, and author network associated with keywords were also illustrated. This study provides an overview for further research related to employee work involvement, especially in the tourism hospitality industry.